Mangrove genera influence bed shear stress and coastal protection ecosystem services - Alice J. Twomey; Dylan Cowley; Simon J. Murphy; David P. Callaghan; Marc Koh; Neil Saintilan; Catherine E. Lovelock (Water Research, 2026)

Global patterns and regional insights into kelp forest protection, restoration, and stewardship - Aaron M. Eger; Adriana Verges; Akshata MehtaFalkland Islands; Albert Pessarrodona; Alejandra Mora-Soto; Alejandro Bernal-Ibáñez; Aleksandra Smorygo; Alexandria M. Niese; Alexis Savard-Drouin; Andrew Kalani Carlson; Ang Put; Annalisa Falace; et al. (Journal of Applied Phycology, 2026)
Kelp forests are among the most extensive and productive coastal ecosystems, yet they remain underrepresented in global conservation policy despite widespread declines driven by interacting global- (i.e., ocean warming, marine heatwaves) to local-scale stressors. At the same time, kelp conservation and restoration efforts are expanding rapidly across regions, but measures of success and syntheses tend to primarily focus on ecological conditions and trends, not on conservation and restoration actions. To fill this gap, we developed a comparative global dataset of kelp conservation initiatives based on expert-derived regional narratives from 209 participants spanning 35 regions with kelp forests. We applied a structured presence–absence scoring framework across six domains: conservation actions, restoration approaches, governance actors, conservation objectives, social dimensions, and funding structures, supplemented by regional expert knowledge to enable cross-regional comparison. Across regions, conservation was characterised by strong emphasis on monitoring (86% of regions), multi-actor governance (scientific institutions 94%, government agencies 86%), and protecting existing forests (66%), while active restoration was undertaken in half of the regions. Social engagement (66%) and links to fisheries and livelihoods (69%) were widespread, whereas explicit climate adaptation objectives were less common (17%). We identify a set of conservation profiles that describe how kelp forest conservation is advancing in different ecological and governance contexts worldwide. These findings highlight that scaling kelp conservation is as dependent on the social, financial, institutional, and policy systems that govern implementation, as it is on ecological knowledge and technical capacity. By bridging regional knowledge with global analysis, this study provides a framework for aligning locally grounded conservation action with global biodiversity targets.

The sensory and ripening characteristics of Cheddar cheese manufactured within a multispecies sward dairy food system - Richard M. Page; Maurice G. O'Sullivan; Brendan Horan; David T. Mannion; Kieran N. Kilcawley; Iwona Skibinska; Alann Jezequel; John T. Tobin; James A. O'Mahony; Tom F. O'Callaghan; Prabin Lamichhane (International Dairy Journal, 2026)

Investigating coral rubble dynamics through tilting base and flume experiments - Wen Deng; Cyprien Simonnet; Lauren Nolan; David P. Callaghan; Tom E. Baldock (Coastal Engineering, 2026)

The impacts of a multispecies sward grazing system and stage of lactation on the processing-efficiency and compositional characteristics of milk and Cheddar cheese - Richard M. Page; Brendan Horan; John T. Tobin; David T. Mannion; Kieran N. Kilcawley; Iwona Skibinska; Alann Jezequel; James A. O'Mahony; Tom F. O'Callaghan; Prabin Lamichhane (International Dairy Journal, 2025)

Interdisciplinary solutions to enable nature-based solutions for coastal protection achieve ecological and engineering outcomes - Alice J. Twomey; Katherine Erickson; Melanie J. Bishop; Kris Boody; David P. Callaghan; Toni Cannard; Catherine E. Lovelock; Mariana Mayer-Pinto; Rebecca L. Morris; Andrew W.M. Pomeroy; Megan I. Saunders; Andy Steven; et al. (Environmental Science & Policy, 2025)

Discoveries on coastal retrogressive breach failures inspired by failure of an underwater fixed platform - Xiamei Man; William R. Dally; David P. Callaghan; Peter Nielsen (Marine Geology, 2025)

Quantifying the impact of future climate change on the risk of coral rubble instability across the Great Barrier Reef by 2100 - Dongfang Liu; David P. Callaghan; Tom E. Baldock (Journal of Environmental Management, 2025)

Bio-degradable ‘reef bags’ used for rubble stabilisation and their impact on rubble stability, binding, coral recruitment and fish occupancy - Tania M. Kenyon; Conor Jones; David Rissik; Wills Brassil; David Callaghan; Neil Mattocks; Tom E. Baldock (Ecological Engineering, 2025)

A probabilistic coral rubble mechanical instability model applied with field observations from the Great Barrier reef - Dongfang Liu; David P. Callaghan; Ananth Wuppukondur; Tom E. Baldock (Coastal Engineering, 2025)

Structural and hydrodynamic modelling of the probability of breakage of branching and plate coral colonies - Wen Deng; Tania Kenyon; Karen Eigeland; David P. Callaghan; Tom E. Baldock (Coastal Engineering, 2025)

Measurements of particulate methanesulfonic acid above the remote Arctic Ocean using a high resolution aerosol mass spectrometer - Yangmei Zhang; Junying Sun; Xiaojing Shen; Vipul Lal Chandani; Mao Du; Congbo Song; Yuqing Dai; Guoyuan Hu; Mingxi Yang; Gavin H. Tilstone; Tom Jordan; Giorgio Dall’Olmo; et al. (Atmospheric Environment, 2024)

Response to the detection of Fusarium dieback associated with ambrosia beetles on Acer negundo in New South Wales - Sophia Callaghan; Angus J. Carnegie; Peter Gillespie; Shannon Mulholland; Matthew Nagel; David Sargeant; Andrew Daly; Ossie Wildman (Australasian Plant Pathology, 2024)
Symptoms consistent with polyphagous shot hole borer ( Euwallacea fornicatus ) and Fusarium dieback ( Fusarium euwallaceae ), recognised as high priority environmental pests for Australia, were observed on a single box elder ( Acer negundo) tree in Sydney, New South Wales, in March 2022 during routine forest biosecurity surveillance. Delimiting surveys were undertaken around the Sydney basin, extending radially from the original box elder, resulting in the detection of a further three box elder and one tuckeroo ( Cupaniopsis anacardioides ) with suspicious symptoms. Samples were taken from the five trees and associated beetles diagnosed using morphological and molecular methods. Associated Fusarium -like fungi were identified according to phylogenetic inference using regions of the internal transcribed spacer, as well as the translation elongation factor 1-α and RNA polymerase II genes. The tea shot hole borer, Euwallacea perbrevis , was identified along with its known fungal mutualist, Fusarium obliquiseptatum . This pair have been reported in Queensland on avocado ( Persea americana ) and tuckeroo, and there are unpublished records of E. perbrevis from northern NSW, but this is the first report of both species occurring simultaneously in NSW. The biosecurity response following the initial detection, including the establishment of an Incident Management Team, surveillance, diagnostics, and stakeholder engagement, is discussed. This paper highlights the importance of surveillance for early detection of invasive pests and biosecurity systems and processes for enabling a timely response.

Host response signature trends in persistent bacteraemia and metastatic infection due to Staphylococcus aureus and Gram-negative bacilli: a prospective multicentre observational study - Anna Maria Peri; Nastaran Rafiei; Kevin O’Callaghan; Anna Brischetto; Bianca Graves; Holly Sinclair; Matthew Eustace; Karen Lim; Jill Parkes-Smith; Adam Stewart; Natalie Davidson; Alexis Tabah; et al. (Infectious Diseases, 2024)

The links between marine plastic litter and the air-sea flux of greenhouse gases - Lonneke Goddijn-Murphy; David K. Woolf; Ryan Pereira; Christa A. Marandino; Adrian H. Callaghan; Jacek Piskozub (Frontiers in Marine Science, 2023)
Climate change and plastic pollution are two of the most pressing environmental challenges caused by human activity, and they are directly and indirectly linked. We focus on the relationship between marine plastic litter and the air-sea flux of greenhouse gases (GHGs). Marine plastic litter has the potential to both enhance and reduce oceanic GHG fluxes, but this depends on many factors that are not well understood. Different kinds of plastic behave quite differently in the sea, affecting air-sea gas exchange in different, largely unknown, ways. The mechanisms of air-sea exchange of GHGs have been extensively studied and if air-sea gas transfer coefficients and concentrations of the gas in water and air are known, calculating the resulting GHG fluxes is reasonably straightforward. However, relatively little is known about the consequences of marine plastic litter for gas transfer coefficients, concentrations, and fluxes. Here we evaluate the most important aspects controlling the exchange of GHGs between the sea and the atmosphere and how marine plastic litter could change these. The aim is to move towards improving air-sea GHG flux calculations in the presence of plastic litter and we have largely limited ourselves to identifying processes, rather than estimating relative importance.

Using valve gape analysis to compare sensitivity of native Mytilus edulis to invasive Magallana gigas when exposed to heavy metal contamination - David B. Kelleghan; Luke O'Callaghan; Freddie Huggard; Tasman P. Crowe; Paul R. Brooks (Marine Environmental Research, 2023)

Logistical considerations and challenges in deploying virtual biomethane pipelines to serve on-farm biogas plants - Dónal Ó Céileachair; Seán O'Callaghan; David M. Wall; David Goulding; Declan O'Connor; Jerry D. Murphy; Richard O'Shea (Journal of Cleaner Production, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Phenotypic plasticity as a cause and consequence of population dynamics - Dominic P. Brass; Christina A. Cobbold; David A. Ewing; Bethan V. Purse; Amanda Callaghan; Steven M. White (Ecology Letters, 2021)
Predicting complex species‐environment interactions is crucial for guiding conservation and mitigation strategies in a dynamically changing world. Phenotypic plasticity is a mechanism of trait variation that determines how individuals and populations adapt to changing and novel environments. For individuals, the effects of phenotypic plasticity can be quantified by measuring environment–trait relationships, but it is often difficult to predict how phenotypic plasticity affects populations. The assumption that environment–trait relationships validated for individuals indicate how populations respond to environmental change is commonly made without sufficient justification. Here we derive a novel general mathematical framework linking trait variation due to phenotypic plasticity to population dynamics. Applying the framework to the classical example of Nicholson's blowflies, we show how seemingly sensible predictions made from environment–trait relationships do not generalise to population responses. As a consequence, trait‐based analyses that do not incorporate population feedbacks risk mischaracterising the effect of environmental change on populations.

Corrigendum: OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2021)

The missing pieces for better future predictions in subarctic ecosystems: A Torneträsk case study - Didac Pascual; Jonas Åkerman; Marina Becher; Terry V. Callaghan; Torben R. Christensen; Ellen Dorrepaal; Urban Emanuelsson; Reiner Giesler; Dan Hammarlund; Edward Hanna; Annika Hofgaard; Hongxiao Jin; et al. (Ambio, 2021)
Arctic and subarctic ecosystems are experiencing substantial changes in hydrology, vegetation, permafrost conditions, and carbon cycling, in response to climatic change and other anthropogenic drivers, and these changes are likely to continue over this century. The total magnitude of these changes results from multiple interactions among these drivers. Field measurements can address the overall responses to different changing drivers, but are less capable of quantifying the interactions among them. Currently, a comprehensive assessment of the drivers of ecosystem changes, and the magnitude of their direct and indirect impacts on subarctic ecosystems, is missing. The Torneträsk area, in the Swedish subarctic, has an unrivalled history of environmental observation over 100 years, and is one of the most studied sites in the Arctic. In this study, we summarize and rank the drivers of ecosystem change in the Torneträsk area, and propose research priorities identified, by expert assessment, to improve predictions of ecosystem changes. The research priorities identified include understanding impacts on ecosystems brought on by altered frequency and intensity of winter warming events, evapotranspiration rates, rainfall, duration of snow cover and lake-ice, changed soil moisture, and droughts. This case study can help us understand the ongoing ecosystem changes occurring in the Torneträsk area, and contribute to improve predictions of future ecosystem changes at a larger scale. This understanding will provide the basis for the future mitigation and adaptation plans needed in a changing climate.

Seagrass losses since mid‐20th century fuelled CO 2 emissions from soil carbon stocks - Cristian Salinas; Carlos M. Duarte; Paul S. Lavery; Pere Masque; Ariane Arias‐Ortiz; Javier X. Leon; David Callaghan; Gary A. Kendrick; Oscar Serrano (Global Change Biology, 2020)
Seagrass meadows store globally significant organic carbon (C org ) stocks which, if disturbed, can lead to CO 2 emissions, contributing to climate change. Eutrophication and thermal stress continue to be a major cause of seagrass decline worldwide, but the associated CO 2 emissions remain poorly understood. This study presents comprehensive estimates of seagrass soil C org erosion following eutrophication‐driven seagrass loss in Cockburn Sound (23 km 2 between 1960s and 1990s) and identifies the main drivers. We estimate that shallow seagrass meadows ( org stocks in 50 cm thick soils (4.5 ± 0.7 kg C org /m 2 ) than previously vegetated counterparts (0.5 ± 0.1 kg C org /m 2 ). In deeper areas (>5 m), however, soil C org stocks in seagrass and bare but previously vegetated areas were not significantly different (2.6 ± 0.3 and 3.0 ± 0.6 kg C org /m 2 , respectively). The soil C org sequestration capacity prevailed in shallow and deep vegetated areas (55 ± 11 and 21 ± 7 g C org m −2 year −1 , respectively), but was lost in bare areas. We identified that seagrass canopy loss alone does not necessarily drive changes in soil C org but, when combined with high hydrodynamic energy, significant erosion occurred. Our estimates point at ~0.20 m/s as the critical shear velocity threshold causing soil C org erosion. We estimate, from field studies and satellite imagery, that soil C org erosion (within the top 50 cm) following seagrass loss likely resulted in cumulative emissions of 0.06–0.14 Tg CO 2‐eq over the last 40 years in Cockburn Sound. We estimated that indirect impacts (i.e. eutrophication, thermal stress and light stress) causing the loss of ~161,150 ha of seagrasses in Australia, likely resulted in the release of 11–21 Tg CO 2 ‐eq since the 1950s, increasing cumulative CO 2 emissions from land‐use change in Australia by 1.1%–2.3% per annum. The patterns described serve as a baseline to estimate potential CO 2 emissions following disturbance of seagrass meadows.

Habitat maps to enhance monitoring and management of the Great Barrier Reef - Chris M. Roelfsema; Eva M. Kovacs; Juan Carlos Ortiz; David P. Callaghan; Karlo Hock; Mathieu Mongin; Kasper Johansen; Peter J. Mumby; Magnus Wettle; Mike Ronan; Petra Lundgren; Emma V. Kennedy; et al. (Coral Reefs, 2020)

OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2019)
The OceanGliders program started in 2016 to support active coordination and enhancement of global glider activity. OceanGliders contributes to the international efforts of the Global Ocean Observation System (GOOS) for Climate, Ocean Health, and Operational Services. It brings together marine scientists and engineers operating gliders around the world: (1) to observe the long-term physical, biogeochemical, and biological ocean processes and phenomena that are relevant for societal applications; and, (2) to contribute to the GOOS through real-time and delayed mode data dissemination. The OceanGliders program is distributed across national and regional observing systems and significantly contributes to integrated, multi-scale and multi-platform sampling strategies. OceanGliders shares best practices, requirements, and scientific knowledge needed for glider operations, data collection and analysis. It also monitors global glider activity and supports the dissemination of glider data through regional and global databases, in real-time and delayed modes, facilitating data access to the wider community. OceanGliders currently supports national, regional and global initiatives to maintain and expand the capabilities and application of gliders to meet key global challenges such as improved measurement of ocean boundary currents, water transformation and storm forecast.

The chemical coding of 5-hydroxytryptamine containing enteroendocrine cells in the mouse gastrointestinal tract - Yohan Reynaud; Josiane Fakhry; Linda Fothergill; Brid Callaghan; Mitchell Ringuet; Billie Hunne; David M. Bravo; John B. Furness (Cell and Tissue Research, 2016)

Globalisation, the founder effect, hybrid Phytophthora species and rapid evolution: new headaches for biosecurity - Sophia Callaghan; David Guest (Australasian Plant Pathology, 2015)

Differences in hormone localisation patterns of K and L type enteroendocrine cells in the mouse and pig small intestine and colon - Hyun-Jung Cho; Samin Kosari; Billie Hunne; Brid Callaghan; Leni R. Rivera; David M. Bravo; John B. Furness (Cell and Tissue Research, 2015)

Metabolic Alterations During the Growth of Tumour Spheroids - Katarzyna Bloch; Hannah Smith; Victoria Hamel Parsons; David Gavaghan; Catherine Kelly; Alexander Fletcher; Philip Maini; Richard Callaghan (Cell Biochemistry and Biophysics, 2014)

Identification of enteroendocrine cells that express TRPA1 channels in the mouse intestine - Hyun-Jung Cho; Brid Callaghan; Romke Bron; David M. Bravo; John B. Furness (Cell and Tissue Research, 2014)

Correlation of Hemodynamic Parameters to Endothelial Cell Proliferation in an End to Side Anastomosis - Leonard D. Browne; Siobhan O’Callaghan; David A. Hoey; Philip Griffin; Timothy M. McGloughlin; Michael T. Walsh (Cardiovascular Engineering and Technology, 2014)

Coastal retreat and improved water quality mitigate losses of seagrass from sea level rise - Megan I. Saunders; Javier Leon; Stuart R. Phinn; David P. Callaghan; Katherine R. O'Brien; Chris M. Roelfsema; Catherine E. Lovelock; Mitchell B. Lyons; Peter J. Mumby (Global Change Biology, 2013)
The distribution and abundance of seagrass ecosystems could change significantly over the coming century due to sea level rise ( SLR ). Coastal managers require mechanistic understanding of the processes affecting seagrass response to SLR to maximize their conservation and associated provision of ecosystem services. In Moreton Bay, Queensland, Australia, vast seagrass meadows supporting populations of sea turtles and dugongs are juxtaposed with the multiple stressors associated with a large and rapidly expanding human population. Here, the interactive effects of predicted SLR , changes in water clarity, and land use on future distributions of seagrass in Moreton Bay were quantified. A habitat distribution model of present day seagrass in relation to benthic irradiance and wave height was developed which correctly classified habitats in 83% of cases. Spatial predictions of seagrass and presence derived from the model and bathymetric data were used to initiate a SLR inundation model. Bathymetry was iteratively modified based on SLR and sedimentary accretion in seagrass to simulate potential seagrass habitat at 10 year time steps until 2100. The area of seagrass habitat was predicted to decline by 17% by 2100 under a scenario of SLR of 1.1 m. A scenario including the removal of impervious surfaces, such as roads and houses, from newly inundated regions, demonstrated that managed retreat of the shoreline could potentially reduce the overall decline in seagrass habitat to just 5%. The predicted reduction in area of seagrass habitat could be offset by an improvement in water clarity of 30%. Greater improvements in water clarity would be necessary for larger magnitudes of SLR . Management to improve water quality will provide present and future benefits to seagrasses under climate change and should be a priority for managers seeking to compensate for the effects of global change on these valuable habitats.

CCL27–CCR10 and CXCL12–CXCR4 chemokine ligand-receptor mRNA expression ratio: new predictive factors of tumor progression in cutaneous malignant melanoma - Carlos Monteagudo; David Ramos; Ana Pellín-Carcelén; Rosario Gil; Robert C. Callaghan; José M. Martín; Vicent Alonso; Amelia Murgui; Lara Navarro; Silvia Calabuig; José Antonio López-Guerrero; Esperanza Jordá; et al. (Clinical & Experimental Metastasis, 2012)

Enhanced UV-B and Elevated CO2 Impacts Sub-Arctic Shrub Berry Abundance, Quality and Seed Germination - Dylan Gwynn-Jones; Alan G. Jones; Alice Waterhouse; Ana Winters; David Comont; John Scullion; Rosie Gardias; Bente J. Graee; John A. Lee; Terry V. Callaghan (Ambio, 2012)

Estimating coastal recession due to sea level rise: beyond the Bruun rule - Roshanka Ranasinghe; David Callaghan; Marcel J. F. Stive (Climatic Change, 2012)

Global assessment of experimental climate warming on tundra vegetation: heterogeneity over space and time - Sarah C. Elmendorf; Gregory H. R. Henry; Robert D. Hollister; Robert G. Björk; Anne D. Bjorkman; Terry V. Callaghan; Laura Siegwart Collier; Elisabeth J. Cooper; Johannes H. C. Cornelissen; Thomas A. Day; Anna Maria Fosaa; William A. Gould; et al. (Ecology Letters, 2012)
Ecology Letters (2011) Abstract Understanding the sensitivity of tundra vegetation to climate warming is critical to forecasting future biodiversity and vegetation feedbacks to climate. In situ warming experiments accelerate climate change on a small scale to forecast responses of local plant communities. Limitations of this approach include the apparent site‐specificity of results and uncertainty about the power of short‐term studies to anticipate longer term change. We address these issues with a synthesis of 61 experimental warming studies, of up to 20 years duration, in tundra sites worldwide. The response of plant groups to warming often differed with ambient summer temperature, soil moisture and experimental duration. Shrubs increased with warming only where ambient temperature was high, whereas graminoids increased primarily in the coldest study sites. Linear increases in effect size over time were frequently observed. There was little indication of saturating or accelerating effects, as would be predicted if negative or positive vegetation feedbacks were common. These results indicate that tundra vegetation exhibits strong regional variation in response to warming, and that in vulnerable regions, cumulative effects of long‐term warming on tundra vegetation – and associated ecosystem consequences – have the potential to be much greater than we have observed to date.

Multiple Effects of Changes in Arctic Snow Cover - Terry V. Callaghan; Margareta Johansson; Ross D. Brown; Pavel Ya. Groisman; Niklas Labba; Vladimir Radionov; Raymond S. Bradley; Sylvie Blangy; Olga N. Bulygina; Torben R. Christensen; Jonathan E. Colman; Richard L. H. Essery; et al. (Ambio, 2011)

The Changing Face of Arctic Snow Cover: A Synthesis of Observed and Projected Changes - Terry V. Callaghan; Margareta Johansson; Ross D. Brown; Pavel Ya. Groisman; Niklas Labba; Vladimir Radionov; Roger G. Barry; Olga N. Bulygina; Richard L. H. Essery; D. M. Frolov; Vladimir N. Golubev; Thomas C. Grenfell; et al. (Ambio, 2011)

Multi-Decadal Changes in Tundra Environments and Ecosystems: Synthesis of the International Polar Year-Back to the Future Project (IPY-BTF) - Terry V. Callaghan; Craig E. Tweedie; Jonas Åkerman; Christopher Andrews; Johan Bergstedt; Malcolm G. Butler; Torben R. Christensen; Dorothy Cooley; Ulrika Dahlberg; Ryan K. Danby; Fred J. A. Daniёls; Johannes G. de Molenaar; et al. (Ambio, 2011)

CyberShake: A Physics-Based Seismic Hazard Model for Southern California - Robert Graves; Thomas H. Jordan; Scott Callaghan; Ewa Deelman; Edward Field; Gideon Juve; Carl Kesselman; Philip Maechling; Gaurang Mehta; Kevin Milner; David Okaya; Patrick Small; et al. (Pure and Applied Geophysics, 2011)

Deficiency in the divalent metal transporter 1 increases bleomycin-induced lung injury - Funmei Yang; Jacqueline G. Stonehuerner; Judy H. Richards; Ngoc-Bich Nguyen; Kimberly D. Callaghan; David J. Haile; Andrew J. Ghio (BioMetals, 2010)

Plant species traits are the predominant control on litter decomposition rates within biomes worldwide - William K. Cornwell; Johannes H. C. Cornelissen; Kathryn Amatangelo; Ellen Dorrepaal; Valerie T. Eviner; Oscar Godoy; Sarah E. Hobbie; Bart Hoorens; Hiroko Kurokawa; Natalia Pérez‐Harguindeguy; Helen M. Quested; Louis S. Santiago; et al. (Ecology Letters, 2008)
Worldwide decomposition rates depend both on climate and the legacy of plant functional traits as litter quality. To quantify the degree to which functional differentiation among species affects their litter decomposition rates, we brought together leaf trait and litter mass loss data for 818 species from 66 decomposition experiments on six continents. We show that: (i) the magnitude of species‐driven differences is much larger than previously thought and greater than climate‐driven variation; (ii) the decomposability of a species’ litter is consistently correlated with that species’ ecological strategy within different ecosystems globally, representing a new connection between whole plant carbon strategy and biogeochemical cycling. This connection between plant strategies and decomposability is crucial for both understanding vegetation–soil feedbacks, and for improving forecasts of the global carbon cycle.

Global negative vegetation feedback to climate warming responses of leaf litter decomposition rates in cold biomes - Johannes H.C. Cornelissen; Peter M. Van Bodegom; Rien Aerts; Terry V. Callaghan; Richard S.P. Van Logtestijn; Juha Alatalo; F. Stuart Chapin; Renato Gerdol; Jon Gudmundsson; Dylan Gwynn‐Jones; Anne E. Hartley; David S. Hik; et al. (Ecology Letters, 2007)
Whether climate change will turn cold biomes from large long‐term carbon sinks into sources is hotly debated because of the great potential for ecosystem‐mediated feedbacks to global climate. Critical are the direction, magnitude and generality of climate responses of plant litter decomposition. Here, we present the first quantitative analysis of the major climate‐change‐related drivers of litter decomposition rates in cold northern biomes worldwide. Leaf litters collected from the predominant species in 33 global change manipulation experiments in circum‐arctic‐alpine ecosystems were incubated simultaneously in two contrasting arctic life zones. We demonstrate that longer‐term, large‐scale changes to leaf litter decomposition will be driven primarily by both direct warming effects and concomitant shifts in plant growth form composition, with a much smaller role for changes in litter quality within species. Specifically, the ongoing warming‐induced expansion of shrubs with recalcitrant leaf litter across cold biomes would constitute a negative feedback to global warming. Depending on the strength of other (previously reported) positive feedbacks of shrub expansion on soil carbon turnover, this may partly counteract direct warming enhancement of litter decomposition.

Symposia lectures - F. Parak; A. Ostermann; G. U. Nienhaus; Nobuo Niimura; William A. Eaton; Stephen J. Hagen; Eric R. Henry; James Hofrichter; Gouri Jas; Lisa Lapidus; Victor Muñoz; Chih-chen Wang; et al. (Journal of Biosciences, 1999)

Oral vaccination - Gordon Dougan; Duncan Maskell; David O'Callaghan; Steve Chatfield; Ian Charles; Carlos Hormaeche (Antonie van Leeuwenhoek, 1988)